CAREER RESILIENCE, MENTAL HELATH AND SUBJECTIVE WELLBEING OF HELPING PROFESSIONAL AT WORKPLACE TOWARDS A PROPOSED WELLNESS PROGRAM - Ma Fatima B Bacala (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study was led to identify and explore the relationship between resilience, mental health and subjective well‐being among Helping Professionals and so as to know their experiences, coping strategies and adjustment employed at workplace. The study focused mainly with the professional specifically helping professionals such as, registered counselors, registered psychologists, social workers, doctors, psychiatrist, nurses and policemen/military, Firemen, Jail Officers and Teachers who are all actually based working in the City of Balanga Bataan . A sequential explanatory design was used in this study, using a standardized and validated questionnaire and so as an interview was conducted. The method of snowball technique was used to select Helping Professionals as participants. A survey of 100 helping professionals was conducted to test the hypothesized model. The results obtained from this study are that there is sufficient evidence to prove that mental health status has significant relationship to the level of career resilience. It is also evident that subjective well-being of the employee has significant connection to the mental health status. This study also beneficial both companies, agencies and professionals. The employee wellness program is important to improve employees' career resilience, mental health and subjective well-being, often through preventive self-care.